METHOD FOR PRODUCING Nb ALLOY MEMBER

By using Nb alloy powder containing Hf, Ta and W, combined with additive manufacturing and heat treatment, a specific microstructure is formed, which solves the problems of large residual stress and insufficient mechanical properties in refractory Nb alloys, and achieves high mechanical properties in high temperature environments.

JP2025019927AActive Publication Date: 2025-02-07NTT DATA ZAM TECH INC
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
JP2023123840
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-07-28
Publication Date
2025-02-07
Estimated Expiration
2043-07-28

AI Technical Summary

Technical Problem

In additive manufacturing of high melting point metals such as refractory Nb alloys, the rapid solidification of the cured powder leads to large residual stress, and the existing heat treatment methods cannot fully restore mechanical properties.

Method used

Using Nb alloy powder, containing at least 9% of alloy elements such as Hf, Ta and W, through additive manufacturing, residual stress removal and solubilization, a specific microstructure is formed, including columnar grains and oxide precipitation, and the heat treatment temperature and time are controlled.

Benefits of technology

The mechanical properties of refractory Nb alloys are significantly improved and are suitable for high temperature environments, especially engine components in the aerospace field.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025019927000001_ABST
    Figure 2025019927000001_ABST
Patent Text Reader

Abstract

To produce a refractory Nb alloy member having more excellent mechanical properties using additive manufacturing.SOLUTION: There is provided a method for producing a Nb alloy member including the steps of: preparing alloy powder of a refractory Nb alloy member containing a total of 9 mass% or more of one or more alloy elements selected from Hf, Ta, and W; layering the alloy powder using additive manufacturing technology to form a shaped object; subjecting the shaped object to heat treatment at a temperature of 1050°C or more and 1150°C or less to remove residual stress; and subjecting the shaped object to heat treatment at a temperature of 1300°C or more and 1500°C or less to subject to solution treatment.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a method for producing a component made of a refractory Nb alloy by additive manufacturing and heat treatment, and to said component. [Background technology]

[0002] Refractory Nb alloys are made mainly of Nb, a high-melting metal, and are used in engine parts exposed to high temperatures in the aerospace industry. Refractory Nb alloy parts that are in practical use are generally formed by cutting ingots or forged bars. However, in many cases, more than 90% of the material is removed from the material to the final product, which creates a cost issue. In response to this, in recent years, there has been active research and development into the production of refractory Nb alloy parts by additive manufacturing, focusing on the characteristic that complex shapes can be formed from powder materials.

[0003] For example, Non-Patent Document 1 describes additive manufacturing of C103, the most popular refractory Nb alloy, by laser powder bed fusion (L-PBF), followed by residual stress relief treatment at 1100°C and hot isostatic pressing (HIP). Non-Patent Document 2 describes additive manufacturing of C103 alloy by L-PBF, followed by heat treatment at 1000°C to remove residual stress. Patent Document 1 also describes niobium alloy powder that can be used as a raw material for additive manufacturing. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] JP 2023-078274 A [Non-patent literature]

[0005] [Non-Patent Document 1] OR Mireles et al., "Additive Manufacture of Refractory Alloy C103 for Propulsion Applications," AIAA Propulsion and Energy 2020 Forum, American Institute of Aeronautics and Astronautics, August 2020. [Non-Patent Document 2] PD Awasthi et al., "Mechanical properties and microstructural characteristics of additively manufactured C103 niobium alloy," Materials Science & Engineering A, Elsevier BV, Volume 831, January 2022, Publication number 142183 Summary of the Invention [Problem to be solved by the invention]

[0006] In additive manufacturing of high-melting-point metals such as refractory Nb alloys, the molten powder solidifies rapidly, leaving large residual stress after molding, so heat treatment to remove the residual stress is essential. However, the inventors have found through experiments that simply removing the residual stress does not sufficiently restore the mechanical properties, and there is room for further improvement in the heat treatment method after additive manufacturing.

[0007] The present invention has been made in consideration of the above, and aims to provide a method for producing a refractory Nb alloy component having superior mechanical properties by utilizing additive manufacturing. [Means for solving the problem]

[0008] The method for producing a Nb alloy part of the present invention includes the steps of preparing an alloy powder of a refractory Nb alloy containing one or more alloying elements selected from Hf, Ta, and W in a total amount of 9 mass% or more, stacking the alloy powder by an additive manufacturing technique to form a shaped object, heat treating the shaped object at 1050°C or more and 1150°C or less to remove residual stress, and heat treating the shaped object at 1300°C or more and 1500°C or less to bring it into solution.

[0009] Preferably, the alloy powder has a representative composition by mass of Nb-10Hf-1Ti. Alternatively, the alloy powder has a representative composition by mass of Nb-28Ta-10W-1Zr. Alternatively, the alloy powder has a representative composition by mass of Nb-28Ta-5W-1Zr.

[0010] The Nb alloy member of the present invention is made of a refractory Nb alloy containing one or more alloying elements selected from Hf, Ta and W in a total amount of 9 mass% or more, and has an average distance between two parallel lines sandwiching a crystal grain in a cross section of 5 to 45 μm, columnar cells with a diameter of 0.1 to 1.0 μm inside the crystal grain, and oxide precipitates of the alloying elements precipitated at the grain boundaries of the crystal grains.

[0011] For example, in the above Nb alloy member, the refractory Nb alloy contains 9 mass% or more of Hf, and the precipitates are oxides of Hf. Alternatively, for example, in the above Nb alloy member, the refractory Nb alloy contains 25 mass% or more of Ta, 4 mass% or more of W, and 0.5 mass% or more of Zr, and the precipitates are oxides of Zr. Effect of the Invention

[0012] According to the method for producing the Nb alloy component of the present invention, additive manufacturing can be used to obtain better mechanical properties. [Brief description of the drawings]

[0013] [Figure 1] FIG. 2 is a process flow diagram of a method for producing a Nb alloy member according to one embodiment. [Diagram 2] This is an SEM image of the as-printed material. [Diagram 3] FIG. 1 shows the results of a cantilever test. [Figure 4] These are the results of tensile tests at room temperature on the as-formed material, and the results of tensile tests at room temperature to high temperatures on the material after residual stress relief. [Diagram 5] FIG. 1 is an EBSD diagram showing the change in crystal grains of a CP-Nb molded object due to heat treatment. [Figure 6] FIG. 1 is an EBSD diagram showing the change in crystal grains of a C103 molded object due to heat treatment. [Figure 7] This is an EBSD diagram showing the change in crystal grains of an FS85 molded object due to heat treatment. [Figure 8] FIG. 13 is an EBSD diagram showing the change in crystal grains of an FS85-5W molded object due to heat treatment. [Figure 9] These are SEM images of the as-printed material and C103 printed objects with different heat treatment conditions. [Figure 10] These are SEM-EDX images of C103 objects molded under different heat treatment conditions. [Figure 11] This is an SEM image of an FS85 component that has been stress relieved and solution treated. [Figure 12] This is an SEM-EDX image of an FS85 component that has been subjected to stress relief treatment and solution treatment. [Figure 13] This is an SEM image of an FS85-5W component that has been stress-relieved and solution-treated. [Figure 14] This is an SEM-EDX image of an FS85-5W component that has been subjected to stress relief treatment and solution treatment. [Figure 15] 4 shows the results of tensile tests at room temperature on test pieces subjected to different heat treatment conditions. [Figure 16] These are the results of tensile tests at high temperatures in a vacuum on Nb alloy members that had been subjected to stress relief treatment and solution treatment. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0014] One embodiment of the method for producing a Nb alloy member according to the present invention will be described with reference to the process flow shown in FIG.

[0015] The refractory Nb alloy powder used in this embodiment contains Nb as the main component and one or more alloying elements selected from Hf, Ta and W in a total amount of 9 mass% or more. Hf, Ta and W all improve the strength of the Nb alloy by solid solution strengthening. On the other hand, in the refractory Nb alloy powder, the total amount of one or more alloying elements selected from Hf, Ta and W is preferably 40 mass% or less. This is because if there are too many solid solution strengthening elements, ductility is easily lost. The refractory Nb alloy powder preferably contains one or more alloying elements selected from Ti and Zr in a total amount of 0.5 to 1.5 mass%. Ti and Zr, together with Hf, form oxides in preference to Nb, thereby improving the oxidation resistance of the alloy at high temperatures.

[0016] An example of such a refractory Nb alloy is the C103 alloy, whose representative composition by mass is expressed as "Nb-10Hf-1Ti". The C103 alloy is the most widely used refractory Nb alloy. The C103 alloy usually has a composition by mass of Hf: 9-11%, Ti: 0.7-1.3%, and the balance: Nb and unavoidable impurities. Representative unavoidable impurities include Zr: 0.7% or less, Ta: 0.5% or less, and W: 0.5% or less.

[0017] Another example of a refractory Nb alloy is the FS85 alloy, whose representative composition by mass is expressed as "Nb-28Ta-10W-1Zr". The FS85 alloy usually has a composition by mass of Ta: 26-29%, W: 10-12%, Zr: 0.6-1.1%, and the balance: Nb and unavoidable impurities.

[0018] Yet another example of a refractory Nb alloy is one whose representative composition by mass is "Nb-28Ta-5W-1Zr", which is an FS85 alloy with the W content reduced to 4-6 mass%. This alloy will be referred to as "FS85-5W" below.

[0019] The grain size of the alloy powder is preferably 10 to 100 μm, more preferably 20 to 60 μm, in terms of the volume-based median value (d50) of the grain size measured by a laser diffraction / scattering method. In addition, it is preferable that the raw material powder for additive manufacturing has a relatively wide grain size distribution so that the filling rate can be increased when forming a thin layer. As a guideline for the grain size distribution width, (d90-d10) is preferably 0.5 to 1.5 times d50. Note that d10, d50, and d90 represent the grain sizes at the points where the cumulative curve is 10%, 50%, and 90%, respectively, when the total volume is 100%.

[0020] The alloy powder is used to form a component using additive manufacturing technology. The additive manufacturing method preferably used is selective laser manufacturing (SLM). The SLM method is a type of powder bed fusion method, in which the raw alloy powder is spread on a modeling stage to form a uniform thin layer, and a laser beam is scanned and irradiated to a predetermined position on the thin layer to melt and solidify the alloy powder, thereby laminating the alloy layers and forming a desired shape.

[0021] Due to the molding method, objects molded by the SLM method contain many columnar crystals extending in the lamination direction of the alloy. Therefore, mechanical properties such as creep differ between the lamination direction and the direction perpendicular to it. In the following, the lamination direction during molding is called the Z direction, and the direction perpendicular to the lamination direction is called the XY direction. In the SLM method, in order to suppress the influence of bias in the scanning direction of the laser light, lamination is performed by rotating the scanning direction by a predetermined angle for each layer, so that the structure of the molded object is isotropic in a plane perpendicular to the Z direction. In this specification, the XY direction only means perpendicular to the Z direction, and does not mean a specific direction in a plane perpendicular to the Z direction.

[0022] Next, the object obtained by additive manufacturing is heat treated to remove residual stress. In additive manufacturing of high-melting-point metals such as refractory Nb alloys, the molten powder solidifies rapidly, resulting in large residual stress after molding. By removing the residual stress, it is possible to prevent the object from cracking during solution treatment (described later) or during processing for finishing the product.

[0023] The treatment temperature for removing residual stress is 1050°C or higher and 1150°C or lower. If the treatment temperature is too low, the residual stress is not sufficiently removed. On the other hand, if the treatment temperature is too high, the molded object may crack while being heated to the treatment temperature. The time for which the molded object is held at the treatment temperature is preferably 30 minutes or higher and 4 hours or lower. If the holding time is too short, the internal temperature may not reach the set temperature depending on the shape of the molded object. On the other hand, a longer holding time has no particular effect and reduces productivity.

[0024] The molded object from which the residual stress has been removed is then subjected to a solution treatment. The solution treatment uniformly dissolves the solute atoms. The solution treatment also rearranges the precipitates in the molded object, stabilizing the structure. The molded object from which the residual stress has been removed may be cooled once and separated from the plate that serves as the base for additive manufacturing, and then heated again to the solution treatment temperature. Alternatively, if the plate has sufficiently high heat resistance, the temperature may be raised to the solution treatment temperature without first cooling.

[0025] The solution treatment temperature is 1300°C or higher, preferably 1350°C or higher, and more preferably 1400°C or higher. The higher the temperature, the faster the solution treatment proceeds. As described below, by performing the solution treatment at 1300°C or higher, precipitates are rearranged and the structure is stabilized. On the other hand, the solution treatment temperature is 1600°C or lower, preferably 1500°C or lower. Even if the solution treatment temperature is higher than this, there is no particular effect and the treatment cost increases.

[0026] After the solution treatment, an aging treatment may be performed at 700 to 900° C. However, if the shaped product is slowly cooled, for example, in a furnace, after the solution treatment, there is no need to perform an aging treatment again.

[0027] The Nb alloy member of the present embodiment is obtained by the additive manufacturing process, residual stress relief process, and solution treatment process described above. The obtained Nb alloy member is then subjected to processes such as polishing, cutting, cleaning, drying, and protective coating for oxidation suppression as necessary to become a final product.

[0028] Next, the structure of the refractory Nb alloy shaped article of this embodiment will be described.

[0029] In the cross section of the crystal grains of the Nb alloy member, the average distance between two parallel lines sandwiching the crystal grain is 5 to 45 μm. The inside of the crystal grains is filled with columnar cells with a diameter of 0.1 to 1.0 μm. The shape and size of these crystal grains and cells are formed during additive manufacturing, and are maintained unchanged even after the subsequent residual stress relief process and solution treatment process. In this specification, the part where the crystal orientation is shifted by 15 degrees or more is defined as the boundary of the crystal grains, and the columnar crystals within the crystal grains where the crystal orientation is shifted by less than 15 degrees are called cells to distinguish them from the crystal grains. Cells are structures formed by cooling during the additive manufacturing process. EXAMPLES

[0030] The method for producing the Nb alloy member and the Nb alloy member of this embodiment will be described in further detail based on experimental results.

[0031] As the refractory Nb alloy powder, powders of C103, FS85, and FS85-5W were used, and the powders were molded by the SLM method using a powder additive manufacturing system (EOS GmbH, M100) equipped with a Yb fiber laser (output 200 W, beam diameter 40 μm), and various heat treatments were performed under different conditions to produce the Nb alloy members of the examples and comparative examples. For comparison, a pure Nb member of the comparative example was produced in the same manner as above using commercially pure Nb (CP-Nb) powder.

[0032] The microstructure of the components was observed using an optical microscope and a scanning electron microscope (SEM). The element distribution was measured during SEM observation using energy dispersive X-ray spectroscopy (SEM-EDX). The grain size and crystal orientation were measured using electron backscatter diffraction (EBSD).

[0033] The mechanical properties of the components were evaluated by tensile tests using 0.2% yield strength, tensile strength, and fracture elongation. In the following, 0.2% yield strength and tensile strength are collectively referred to as "strength," and fracture elongation is simply referred to as "elongation." Tensile tests at room temperature in air were conducted using round test pieces (diameter 3 mm, gauge length 12 mm) in accordance with the ASTM E8-21 standard. The test speed was a stress increase rate of 9 MPa / s up to 0.2% yield strength, and a strain rate of 20% / min thereafter. Tensile tests at 500°C to 1100°C in air were conducted using round test pieces (diameter 3 mm, gauge length 12 mm) in accordance with the ASTM E21-20 standard. The test speed was a strain rate of 0.5% / min up to 0.2% yield strength, and a strain rate of 5% / min thereafter. Tensile tests at 1200-1400°C in a vacuum were performed using flat test pieces (thickness 2.5 mm, width 3 mm, gauge length 16 mm) with an MTS808 type ultra-high temperature material testing machine. The test pieces were heated at a rate of 50°C / min, and after reaching the test temperature, the test was started after holding the temperature for 30 min. The test speed was a crosshead displacement speed of 0.1 mm / min up to 0.2% yield strength, and a crosshead displacement speed of 1 mm / min thereafter.

[0034] The composition and particle size of the powder used are shown in Table 1. Table 2 shows the manufacturing conditions of the parts.

[0035] [Table 1]

[0036] [Table 2]

[0037] First, the as-formed material was evaluated.

[0038] When the cross sections of the as-printed materials were observed under an optical microscope, the structure was dense for all compositions, with no cracks or voids observed. The density of the molded objects was 99.9% or more of the theoretical density for all compositions.

[0039] When the cross sections of the as-printed materials were observed by SEM, the grains were filled with columnar cells with diameters of 0.2 to 0.4 μm in C103, FS85, and FS85-5W, except for CP-Nb (Fig. 2). The reason that the cellular structure was only observed in the alloy composition is thought to be that the fusion of adjacent cells was prevented by precipitates (or non-uniform composition due to segregation) at the cell boundaries.

[0040] When the cross section perpendicular to the Z direction of the as-formed material was measured by EBSD, the body-centered cubic crystals were aligned in the Z direction for all compositions. This result was different from the results in Non-Patent Document 2, in which the

[0001] direction was aligned in the Z direction. For comparison, when CP-Nb powder was used to form the material using a larger powder additive manufacturing system (EOS GmbH, M290. Yb fiber laser output 200 W, beam diameter 40 μm), the

[0001] direction was aligned in the Z direction. Therefore, this difference in crystal orientation is thought to be due to the characteristics of the additive manufacturing equipment, and possibly due to the difference in the direction of heat flow during solidification.

[0041] Next, a cantilever test was performed to evaluate the residual stress during additive manufacturing, and the temperature for residual stress relief treatment was examined. Referring to Figure 3, a shape was created in which two parallel rectangular pieces were connected at one end (far right in Figure 3) and the remaining part was connected by a parallel thin wall. When the thin wall part was cut, the rectangular piece warped and the other end (front left in Figure 3) opened up, and by measuring this opening, the magnitude of the residual stress in the original object could be evaluated. Figure 3 shows the results for the as-printed material and samples that had been treated to relieve residual stress under various conditions. The part with a different color tone from the part at the far right of the sample is the part with the largest distortion.

[0042] From the results in Figure 3, it was found that in CP-Nb, residual stress was almost completely removed by heat treatment at 800℃ for 1 h, in C103, residual stress was significantly reduced by heat treatment at 1000℃ for 1 h and was almost completely removed by heat treatment at 1100℃ for 1 h, and in FS85 and FS85-5W, residual strain was significantly reduced by heat treatment at 1100℃ for 1 h and was almost completely removed by heat treatment at 1100℃ for 2 h.

[0043] Figure 4 and Table 3 show the results of tensile tests at room temperature for the as-printed materials, and the results of tensile tests at temperatures ranging from room temperature to 1100°C using test pieces that had been treated to relieve residual stress. Residual stress relief treatment was performed under the following conditions: 900°C x 1h for CP-Nb, 1100°C x 1h for C103, and 1100°C x 2h for FS85 and FS85-5W.

[0044] All samples exhibited anisotropy that is characteristic of additively manufactured objects. In particular, the alloy samples had extremely small elongation in either or both of the Z and XY directions depending on the test temperature, which may have made them unsuitable for practical use. Comparing the room temperature tensile test results of as-is and stress-relieved materials, stress relief slightly reduced strength and increased elongation for all compositions. For the stress-relieved samples, CP-Nb showed reduced strength and significantly increased elongation at tensile test temperatures of 900°C or higher. For the alloy compositions, a gradual decrease in both strength and elongation was observed as the tensile test temperature increased.

[0045] [Table 3]

[0046] Next, the heat treatment temperature was increased further to observe the structure. The samples were first heated to 1100°C to remove residual stress, and then heated to each temperature. The CP-Nb samples were recrystallized, and the alloy samples were solution-treated. Figures 5 to 8 show the grain boundaries of CP-Nb, C103, FS85, and FS85-5W obtained by EBSD.

[0047] In the case of CP-Nb shown in Figure 5, recrystallization began at 1100°C or higher, and the crystal grains grew large at 1300°C or higher. In addition, although not shown, the measurement results of the crystal orientation showed that the crystal orientation was not uniform at 1400°C, and that the crystal orientation also changed with recrystallization. In the alloy samples shown in Figures 6 to 8, recrystallization did not occur even at 1500°C, and no change was observed in the size or crystal orientation of the crystal grains. The reason why recrystallization did not occur in the alloy samples is thought to be due to the influence of precipitates, which will be described later.

[0048] Table 4 shows the average and standard deviation of the distance between two parallel lines sandwiching a crystal grain in Figures 5 to 8. In Table 4, H is the value in the horizontal direction in Figures 5 to 8, and V is the value in the vertical direction (stacking direction Z) in Figures 5 to 8. In what follows, this distance is referred to as the "grain size in the cross section." Because the cut surface does not pass through the part where the grain size of each crystal grain is at its maximum, the grain size in the cross section is smaller than the actual grain size and there is a large variation, but it does provide a quantitative index of the size of the grains. The grain size in the cross section was between 7.7 and 25.9 μm for the alloy compositions, and was smaller in FS85 and FS85-5W than in C103.

[0049] Since the crystal grain size depends on the laser beam diameter and output, a large powder additive manufacturing system (EOS GmbH, M290) was used to mold CP-Nb and perform residual stress removal treatment at 900°C for 1h. The grain size in the cross section was 22.5μm for H and 33.9μm for V, which was about 1.5 to 1.8 times that of the material with the same composition and heat treatment conditions in Table 4. From this, it is thought that when a large production device is used, the grain size in the cross section will be about 10 to 45μm. In addition, the diameter of the columnar cells filling the crystal grains of the alloy composition is also thought to be about 0.3 to 0.8μm.

[0050] [Table 4]

[0051] SEM images and SEM-EDX images of several alloy samples are shown in Figures 9 to 14. In the SEM-EDX images, areas with high brightness (light color areas) are areas where the element in question is present in large amounts.

[0052] In the SEM image of C103 shown in Figure 9, precipitates can be seen at the grain boundaries and cell boundaries after stress relief treatment at 1100 °C. Furthermore, in the sample that was solution-treated at 1300 °C, the precipitates at the cell boundaries and cell boundaries have disappeared, and the precipitates at the grain boundaries have grown larger. The sample that was solution-treated at 1400 °C appears to maintain the same state as at 1300 °C. The SEM-EDX image of C103 shown in Figure 10 shows that the precipitates at the grain boundaries are oxides of Hf, probably HfO2. Thus, the reason why recrystallization is hindered in C103 by the precipitation of oxides of Hf at the grain boundaries is thought to be because the raw powder used in additive manufacturing contains a lot of oxygen as an impurity. The precipitates at the cell boundaries were small in size, so the components could not be identified by SEM-EDX, but it is possible that Hf and Ti form fine oxides and act as dispersion strengtheners.

[0053] FS85 shown in Figures 11-12 and FS85-5W shown in Figures 13-14 were both stress-relieved at 1100℃×2h and solution-treated at 1400℃×1h. In the SEM images in Figures 11 and 13, both maintained their cell structure, and precipitates at the cell boundaries remained. The SEM-EDX images in Figures 12 and 14 show that the precipitates at the grain boundaries are Zr oxides, probably ZrO2. Thus, the reason why recrystallization is hindered in FS85 and FS85-5W by the precipitation of Zr oxides at the grain boundaries is thought to be because, as in the case of C103, the raw powder used in additive manufacturing contains a large amount of oxygen as an impurity. The precipitates at the cell boundaries were small in size, so the components could not be identified by SEM-EDX, but it is possible that Zr forms fine oxides and acts as a dispersion strengthener.

[0054] The results of tensile tests at room temperature for the as-formed material, the stress-relieved sample, and the stress-relieved and solution-treated sample are shown in Figure 15 and Table 5, and the results of tensile tests at 1000°C are shown in Table 6. For comparison, Figure 15 also shows the values ​​for the forged product described in Non-Patent Document 2. FS85 lacks ductility in the XY directions for the as-formed material and the stress-relieved material, but this is improved by stress relieving and solution treatment. C103 and FS85-5W are ductile even in the as-formed state, making them suitable for forming complex shapes.

[0055] [Table 5]

[0056] [Table 6]

[0057] Next, the alloy samples that had been subjected to residual stress relief treatment at 1100°C for 2 h and solution treatment at 1400°C for 1 h were subjected to tensile tests in a vacuum at 1200 to 1400°C. The results are shown in Figure 16 and Table 7.

[0058] For all compositions, strength gradually decreased and elongation gradually increased as the test temperature increased. Comparing C103 with FS85 and FS85-5W, the former had greater elongation and the latter had greater strength. All compositions were confirmed to have excellent mechanical properties with a good balance between strength and elongation.

[0059] [Table 7]

[0060] From EBSD measurements and SEM observations of alloy samples with different heat treatment conditions, it was found that residual stress can be almost completely removed by heat treatment at about 1100°C, and that the structure can be stabilized by subsequent solution treatment at 1300°C or higher. It was also confirmed that residual stress removal at 1100°C and solution treatment at 1400°C results in excellent mechanical properties that can withstand practical use even in a vacuum at 1200-1400°C.

[0061] The present invention is not limited to the above-described embodiment and examples, and various modifications are possible within the scope of the technical concept thereof.

Claims

1. A step of preparing an alloy powder of a refractory Nb alloy containing one or more alloying elements selected from Hf, Ta, and W in a total amount of 9 mass% or more; depositing the alloy powder by additive manufacturing techniques to form a shaped object; a step of heat treating the shaped object at 1050° C. or more and 1150° C. or less to remove residual stress; a step of subjecting the shaped object to a heat treatment at a temperature of 1300° C. or more and 1500° C. or less to perform a solution treatment; A method for producing a Nb alloy member having the above structure.

2. The alloy powder has a representative composition by mass of Nb-10Hf-1Ti. The method for producing the Nb alloy part according to claim 1.

3. The alloy powder has a representative composition by mass of Nb-28Ta-10W-1Zr. The method for producing the Nb alloy part according to claim 1.

4. The alloy powder has a representative composition by mass of Nb-28Ta-5W-1Zr. The method for producing the Nb alloy part according to claim 1.

5. A refractory Nb alloy containing one or more alloying elements selected from Hf, Ta, and W in a total amount of 9% by mass or more; The average distance between two parallel lines sandwiching a crystal grain in a cross section is 5 to 45 μm; A columnar cell having a diameter of 0.1 to 1.0 μm is present inside the crystal grain; precipitates of oxides of alloying elements precipitated at grain boundaries of the crystal grains; The Nb alloy member has the following structure:

6. The refractory Nb alloy contains 9% by mass or more of Hf, The precipitate is an oxide of Hf. The Nb alloy component according to claim 5.

7. The refractory Nb alloy contains 25% by mass or more of Ta, 4% by mass or more of W, and 0.5% by mass or more of Zr, The precipitate is an oxide of Zr. The Nb alloy component according to claim 5.

Citation Information

Patent Citations

  • Spherical niobium alloy powder, product comprising the same and method for producing the same

    JP2023078274A